1998
DOI: 10.1007/978-1-349-14054-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment in Social Work

Abstract: Any person who does any unauthorised act in relation to this publication may be liable to criminal prosecution and civil claims for damages .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Previous studies have shown that the decisions of child protection workers regarding child safety and permanence were determined more by the parent's level of compliance than by real change (Brank et al 2001;Holland 2000). It was also argued that assessments are often described in a vocabulary that reflects the professional's specialized way of understanding and assessing (Holland 2000), which is seldom the client's world (Milner and O'Byrne 2002;Iversen et al 2005). Platt (2012) suggested an integrated model of parental engagement in child welfare services that takes into account workers' skills and attitudes and various parental and interactional factors.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that the decisions of child protection workers regarding child safety and permanence were determined more by the parent's level of compliance than by real change (Brank et al 2001;Holland 2000). It was also argued that assessments are often described in a vocabulary that reflects the professional's specialized way of understanding and assessing (Holland 2000), which is seldom the client's world (Milner and O'Byrne 2002;Iversen et al 2005). Platt (2012) suggested an integrated model of parental engagement in child welfare services that takes into account workers' skills and attitudes and various parental and interactional factors.…”
Section: Discussionmentioning
confidence: 94%
“…The way in which the downgrading of older casework skills combines with the intensification of workloads to impede the ability to complete the risk assessments with any degree of reliability has been commented on by Milner and O'Byrne (1998). Other research has shown that where there is an environment of institutionalised pressure to complete assessments under conditions of resource constraints and lack of training in traditional casework skills, all manner of subjective judgements creep into assessments (Webb, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…There may be concerns that someone with limited capacity, such as an older person with dementia or someone with severe learning impairment, cannot, as Beckett (2010) suggests, contribute to the exchange. Similarly, both Beckett (2010) and Milner and O'Byrne (2009) suggest that an exchange model may not be feasible in situations of risk. This viewpoint does not take account of the potential for the worker to gain the person's own perspective of risk and, importantly, to gain the perspectives of others in the person's network.…”
Section: Classic Text Reviewmentioning
confidence: 93%